Takayama Confirmative Test for Blood Identification in Stains - Castillo Rodríguez, Nancy Janet (Scientia et Technica, 2019)
The study of blood identification in dry spots using the Takayama crystallographic method is used to support the orientation tests in the forensic laboratories of the Forensic Laboratories of the National Institute of Forensic Medicine and Forensic Sciences. Objetivé: To determine by its crystallographic method its sensitivity, specificity, positive predictive value, negative predictive value, detection limit and concordance index according to different temperature, support and environment conditions. Methodology: 100 samples of dry spots are taken to be double-blinded, on different substrates using the Takayama confirmatory method for blood identification, following the relevant biosecurity measures by the Forensic Biology Laboratory. Results: The statistical values of sensitivity were 92.68%, Specificity 100%, Positive Predictive Value 100%, Negative Predictive Value 95.24%, Detection Limit 1/40 and 100% Concordance Index. Conclusions: Based on the data obtained, the high degree of specificity reveals the effectiveness of the Takayama crystallographic method as confirmatory evidence of support for the presumptive methods of orientation in the identification of blood in spots.